ショウワキチ シュウヘン ニ セイソク スル セイブツ ノ セイタイ ナイ キンゾク ブンセキ - 三島, 昌夫; ミシマ, マサオ; 山県, 登; ヤマガタ, ノボル; 鳥居, 鉄也; トリイ, テツヤ; MISHIMA, Masao; YAMAGATA, Noboru; TORII, Tetsuya (国立極地研究所, 1977)
P(論文) 南極昭和基地周辺に生息するウェッデルアザラシ,アデリーペンギンおよびユキドリの臓器(肺,腎臓および肝臓)中に含まれる微量金属を原子吸光法によって測定した.分析結果の一例として,アデリーペンギンの腎臓に含まれる銅,鉄,亜鉛,カドミウムおよび鉛の濃度はそれぞれ6.5～12.4,188～255,26～43,<0.005～0.002および0.01～0.03μ/g-乾燥重量当たりの範囲であった.銅とカドミウムは測定対象生物のうち,特にユキドリの腎臓に最も濃縮されていた.生物の肺に含まれる金属相互間濃度比は左右の肺で,両者の比は広く分散していた.しかし,ウェッデルアザラシの場合は,両者間の金属濃度比が極めて類似し,Mg/Fe ～0.1,Zn/Fe 0.02～0.03, Pb/Cu 0.01～0.02およびPb/Zn ～0.004であった. Concentrations of trace metals in lung, kidney and liver of Weddell seal, Adelie penguin and snow petrel living around the Syowa Station, Antarctica were determined by atomic absorption methods using flame or flameless system. The results of analysis revealed that the concentration levels of copper, iron, zinc, cadmium and lead in the kidneys of Adelie penguin were ranging 6.5～12.4, 188～255, 26～43, <0.005～0.002 and 0.01～0.03μg per gram dry tissue, respectively. Copper and cadmium were found most concentrated in the kidneys of snow petrels among the animals examined. Concentration ratios of pairs of metals in lungs of animals showed wide ranges both among animals and between right and left lungs except in the case of Weddell seal in which the ratios were exceedingly similar in the both lungs, Mg/Fe being about 0.1, Zn/Fe 0.02～0.03, Pb/Cu 0.01～0.02, and Pb/Zn about 0.004. departmental bulletin paper